Faktor-Faktor Kepuasan Lansia terhadap Tempat Tinggal di Panti Wreda Elim - Salma Novia Nurfarida; Alvina Rahmawati; Wahyu Nugroho; Hilla Zahrotul Habibah; Siti Hikmah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to understand the factors that influence elderly satisfaction in a nursing home environment, focusing on social, physical and psychosocial aspects. Through a qualitative approach, data was collected from in-depth interviews with residents and direct observation at the nursing home, which was then thematically analyzed. The results showed that harmonious social relationships with fellow residents and staff play a crucial role in increasing the sense of security, respect and acceptance of the elderly. In addition, a clean and comfortable physical environment supports their well-being, while the various activities provided help maintain mental and physical health. These findings emphasize the importance of building a family atmosphere and paying attention to the holistic needs of the elderly to improve their quality of life in nursing homes.